Implementasi Penerapan Pedoman Standar Akuntansi Keuangan (PSAK) No. 45 Pada Laporan Keuangan Masjid Di Kelurahan Air Dingin Kecamatan Bukit Raya Kota Pekanbaru - La Ode Syarfan; Indra Safri; Septian Wahyudi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT The purpose of this study was to determine whether the Financial Statements of the Mosque in Simpang Tiga Village covering Al Barokah mosque, Al Marzukin mosque, Al Mulk mosque, Asshobirin mosque, Nurul Hidayah mosque, Subulusalam mosque, and Ar-Raudah Mosque are in accordance with the provisions contained in the Financial Accounting Standards Guidelines (PSAK) No. 45. The research data used in the study are primary data and secondary data. Data obtained directly from the Ar-Raudah mosque management. In this study, the data collection method is by conducting direct observations and interviews with the Ar-Raudah mosque management and documentation. The method of analysis in this study is the Descriptive Qualitative method. The results of this study indicate that of the seven mosques used as research sites, only one mosque has implemented PSAK No. 45, namely the Ashobirin mosque, while the six mosques have not implemented PSAK NO.45, the financial statements are still in the form of simple mosques, namely still in the form of income and expenses not in accordance with PSAK No. 45. This is due to the absence of accounting personnel and not having human resources who understand in the field of accounting. Keywords: Accounting, Financial Statements, Non-Profit Organization, PSAK No.45, Mosque